Fifty years of instrumental surface mass balance observations at Vostok Station, central Antarctica - Alexey A. Ekaykin; Vladimir Ya. Lipenkov; Natalia A. Tebenkova (Journal of Glaciology)
We present the surface mass balance (SMB) dataset from Vostok Station's accumulation stake farms which provide the longest instrumental record of its kind obtained with a uniform technique in central Antarctica over the last 53 years. The snow build-up values at individual stakes demonstrate a strong random scatter related to the interaction of wind-driven snow with snow micro-relief. Because of this depositional noise, the signal-to-noise ratio (SNR) in individual SMB time series derived at single points (from stakes, snow pits or firn cores) is as low as 0.045. Averaging the data over the whole stake farm increases the SNR to 2.3 and thus allows us to investigate reliably the climatic variability of the SMB. Since 1970, the average snow accumulation rate at Vostok has been 22.5 ± 1.3 kg m−2 yr−1. Our data suggest an overall increase of the SMB during the observation period accompanied by a significant decadal variability. The main driver of this variability is local air temperature with an SMB temperature sensitivity of 2.4 ± 0.2 kg m−2 yr−1 K−1 (11 ± 2% K−1). A covariation between the Vostok SMB and the Southern Oscillation Index is also observed.